2021
DOI: 10.1002/1438-390x.12083
|View full text |Cite
|
Sign up to set email alerts
|

Demographic impact of landfill closure on a resident opportunistic gull

Abstract: The management of mixed municipal waste can have an impact on wildlife and ecosystems. Previous studies have investigated how opportunistic species like gulls can react very fast to new landfills; however, the impact of landfill closure on bird populations is less investigated. Yet, there is a need to understand how fast and to what extent, animal populations can be adapted to new scenarios where the waste will not be deposited in landfill sites anymore. The aim is to determine the influence of landfill closur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…For our dataset, dividing the data into shorter resighting periods, like a month, would have led to an overly complex model with little power to provide precise estimates. As our survival estimates are close to those obtained in other independent studies [ 23 , 25 , 32 , 59 , 65 ], we are confident that our results are generally robust. To evaluate this issue more completely, a mark-recapture dataset with more resighting data is required so that models can be run at shorter time intervals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For our dataset, dividing the data into shorter resighting periods, like a month, would have led to an overly complex model with little power to provide precise estimates. As our survival estimates are close to those obtained in other independent studies [ 23 , 25 , 32 , 59 , 65 ], we are confident that our results are generally robust. To evaluate this issue more completely, a mark-recapture dataset with more resighting data is required so that models can be run at shorter time intervals.…”
Section: Discussionsupporting
confidence: 90%
“…Regional differences in survival could be explained by resource variation around the breeding sites. For example, it has been shown that landfill closures can impact YLG population demographics via their effect on juvenile survival [ 59 ]. It is possible that there was a reduction in accessible garbage around Marseille/Hyères during the study period which forced individuals to migrate further, particularly if alternative food sources were not readily available.…”
Section: Discussionmentioning
confidence: 99%
“…Regional differences in survival could be explained by resource variation around the breeding sites. For example, it has been shown that land ll closures can impact YLG population demographics via their effect on juvenile survival [55]. It is possible that there was a reduction in accessible garbage around Marseille/Hyères during the study period which forced individuals to migrate further, particularly if alternative food sources were not readily available.…”
Section: Discussionmentioning
confidence: 99%
“…The conservation campaign in the following years and the White Stork's exploitation of landfills resulted in the rapid recovery of their breeding population in Western Europe (Schulz 1999, Tortosa et al 2002, Massemin-Challet et al 2006). Although many studies discuss the potential effects of change in waste management on species that rely on landfills (see references in Plaza and Lambertucci 2017), only a few have explored the effects of landfill closure, for example, on Yellow-legged Gull ( Larus michahellis ) (Payo-Payo et al 2015, Delgado et al 2021, Pinto et al 2021). In this species, the absence of landfills forced them to shift diet preferences but the scarcity in alternative feeding sources negatively impacted their population dynamics (Steigerwald et al 2015, Zorrozua et al 2020).…”
Section: Introductionmentioning
confidence: 99%